Exposure to 6-PPD Quinone Disrupts Adsorption and Catabolism of Leucine and Causes Mitochondrial Dysfunction in Caenorhabditis elegans - Wei Wang; Yunhui Li; Dayong Wang (Toxics, 2025)
6-PPD quinone (6-PPDQ) is a derivative from 6-PPD, an antioxidant added in tires. Leucine is an important amino acid that needs to be obtained from the diet. In Caenorhabditis elegans, we examined the effect of 6-PPDQ exposure at environmentally relevant concentrations (ERCs) on the content of leucine and underlying mechanisms. In nematodes, 0.1–10 μg/L of 6-PPDQ decreased leucine content. The expression of the aat-1-encoding amino acid transmembrane transporter was decreased by 0.1–10 μg/L of 6-PPDQ, and leucine content was reduced by aat-1 RNAi. Meanwhile, the expression of bcat-1-encoding branched-chain amino acid transferase was increased by 0.1–10 μg/L of 6-PPDQ, and leucine content was increased by bcat-1 RNAi. Additionally, the expressions of dbt-1 and ivd-1 encoding two enzyme genes governing NADH and FADH2 generations were decreased by 0.1–10 μg/L of 6-PPDQ, and their expressions in 6-PPDQ exposed nematodes were increased by bcat-1 RNAi. After 6-PPDQ exposure, NADH content was reduced by dbt-1 RNAi, and FADH2 content was reduced by ivd-1 RNAi. Moreover, 6-PPDQ-induced mitochondrial dysfunction and other aspects of toxicity (such as intestinal ROS generation and lipofuscin accumulation, inhibited locomotion, and reduced brood size) were suppressed by bcat-1 RNAi and strengthened by dbt-1 and ivd-1 RNAi. The 6-PPDQ-induced toxicity and the decrease in dbt-1 and ivd-1 expressions could be inhibited by following leucine (5 mM) treatment. Our results demonstrate the important association of leucine adsorption and catabolism with 6-PPDQ toxicity induction.